2015
DOI: 10.1155/2015/431860
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Trends over Time Using Mann-Kendall and Spearman’s rho Tests in Swat River Basin, Pakistan

Abstract: Accurately predicting precipitation trends is vital in the economic development of a country. This research investigated precipitation variability across 15 stations in the Swat River basin, Pakistan, over a 51-year study period (1961–2011). Nonparametric Mann-Kendall (MK) and Spearman’s rho (SR) statistical tests were used to detect trends in monthly, seasonal, and annual precipitation, and the trend-free prewhitening approach was applied to eliminate serial correlation in the precipitation time series. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
211
0
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(236 citation statements)
references
References 41 publications
12
211
0
13
Order By: Relevance
“…There are many methods to detect the significant trend of the considered meteorological elements in time series of the selected stations, the Mann-Kendall and Spearman's Rho test are most widely used. Many theses have discussed the difference between the Mann-Kendall and Spearman's Rho test [36][37][38], the results show a similar performance of these two methods. In this study we used the M-K method to detect the significant trend and Sen's method to detect trend magnitudes, which were suggested by the World Meteorological Organization [39].…”
Section: Mann-kendall Trend Test and Slop Estimatormentioning
confidence: 78%
“…There are many methods to detect the significant trend of the considered meteorological elements in time series of the selected stations, the Mann-Kendall and Spearman's Rho test are most widely used. Many theses have discussed the difference between the Mann-Kendall and Spearman's Rho test [36][37][38], the results show a similar performance of these two methods. In this study we used the M-K method to detect the significant trend and Sen's method to detect trend magnitudes, which were suggested by the World Meteorological Organization [39].…”
Section: Mann-kendall Trend Test and Slop Estimatormentioning
confidence: 78%
“…This showed that two weather systems influence the precipitation in the Astore sub-basin of the UIB: the Indian summer monsoon (ISM) that bring liquid precipitation during summer [55], and the western disturbances (WDs) that bring solid precipitation during winter and early spring [8,49]. The average annual temperature in the whole Astore basin was found to be significantly (p ≤ 0.05) increasing with Z = 1.75 and the Sen's slope value of 0.041 • C·year −1 and the same temperature trend was observed in the summer (Z = 0.66, Sen's slope = 0.034 • C·year −1 ) and winter (Z = 0.77, Sen's slope = 0.064 • C·year −1 ) seasons.…”
Section: Astore Sub-basinmentioning
confidence: 99%
“…A forma de cálculo de Z está mostrada em diversos textos (p. ex., Ahmad et al, 2015). Sinal positivo (negativo) de Z indica tendência de crescimento (redução).…”
Section: Análise De Tendênciaunclassified